DEVELOPMENT OF NUMERACY LITERACY INSTRUMENTS IN ALGEBRA MATERIAL CLASS X VOCATIONAL SCHOOL - Bastian, Heri; Nindiasari, Hepsi; Sukirwan, Sukirwan (Nindikayla Institute, 2024)
This research aims to produce a Mathematics numeracy literacy instrument on algebra liner material in vocational schools that is tested for validity and reliability, as well as through systematic analysis of instruments with differentiating power tests and difficulty indexes. This type of research is a development study with the Wilson model and the Oriondo and Antonio model. The data collection method uses interviews, expert validation sheets, questionnaires and numeracy literacy tests. The data were analyzed descriptively and quantitatively. The results of the research obtained are: 1) expert assessment states that this numeracy literacy instrument is an instrument that is suitable for use; 2) the readability test shows that this numeracy literacy instrument is categorized as